Numerical Simulation of Effective Properties of 3D Piezoelectric Composites - Ri-Song Qin; Yi Xiao; Haitian Lan (Journal of Engineering)
The prediction of the overall effective properties of fibre-reinforced piezocomposites has drawn much interest from investigators recently. In this work, an algorithm used in two-dimensional (2D) analysis for calculating transversely isotropic material properties is developed. Since the finite element (FE) meshing patterns on the opposite areas are the same, constraint equations can be applied directly to generate appropriate load. The numerical results derived using this model have found a good agreement with those in the literature. The 2D algorithm is then modified and improved in such a way that it is valid for three-dimensional (3D) analysis in the case of random distributed shorts and inclusions. Linear interpolation of displacement field is employed to establish constraint equations of nodal displacements between two adjacent elements.